2002
DOI: 10.1016/s0969-2126(02)00791-8
|View full text |Cite
|
Sign up to set email alerts
|

Noncompetitive Antibody Neutralization of IL-10 Revealed by Protein Engineering and X-Ray Crystallography

Abstract: IL-10 is a dimeric cytokine that must engage its high-affinity cell surface receptor, IL-10R1, to induce multiple cellular activities. Here we report the 1.9 A crystal structure of an engineered IL-10 monomer (IL-10M1) in complex with a neutralizing Fab fragment (9D7Fab). 9D7Fab and IL-10R1 bind distinct nonoverlapping surfaces on IL-10M1. Antagonism of the IL-10M1/IL-10R1 interaction is the result of 9D7Fab-induced conformational changes in the CD loop of IL-10M1 that indirectly alter the structure of the IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Detailed analysis of the scFv-IL-1␤ interface and comparison with other antibody-antigen structures are summarized in Table 1 and supplemental Table 2. The nature of the interface, in particular the high content of aromatic and non-polar residues and the size of the buried surface area, are consistent with a representative sample of previously reported antibody-target protein complexes (35)(36)(37)(38)(39)(40)(41)(42). Of particular importance for the design and humanization of therapeutic antibodies is a knowledge of which residues from the antibody make interactions with the target protein.…”
Section: Discussionsupporting
confidence: 85%
“…Detailed analysis of the scFv-IL-1␤ interface and comparison with other antibody-antigen structures are summarized in Table 1 and supplemental Table 2. The nature of the interface, in particular the high content of aromatic and non-polar residues and the size of the buried surface area, are consistent with a representative sample of previously reported antibody-target protein complexes (35)(36)(37)(38)(39)(40)(41)(42). Of particular importance for the design and humanization of therapeutic antibodies is a knowledge of which residues from the antibody make interactions with the target protein.…”
Section: Discussionsupporting
confidence: 85%
“…1C). As previously described, cIL-10M1 is biologically active, and its structure is identical to one subunit of the cIL-10 dimer (10,22,29). Thus, cIL-10M1 provides an important tool for determining accurate binding parameters for the cIL-10⅐IL-10R1 site 1 interface and for mapping the IL-10R2 binding site.…”
Section: Experimental Strategy To Identify the Il-10r2 Binding Site-mentioning
confidence: 84%
“…To overcome the problem, Josephson et al [44] extended loop DE between Asn116 and Lys117 by insertion of an additional six amino acids (GlyGlyGlySerGlyGly) and showed that the expressed protein folded as a monomer. The crystal structure of monomeric IL-10 [45] confirmed that it is very similar to a single domain of the IL-10 dimer. Further analysis showed that it was able to form a 1:1 complex with IL-10 receptor 1 (IL-10R1); although affinity was 60-fold reduced but the protein still retained biological activity, which was 10-fold lower as compared with the dimeric wild-type IL-10.…”
Section: Monomeric Il-10mentioning
confidence: 65%